DESAIN FORMULASI PENILAIAN KINERJA KESEHATAN FISKAL DAN PENGELOLAAN KEUANGAN DAERAH (STUDI KASUS PROVINSI JAWA BARAT) - M. Iqbal (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2017)
The background of this research was the presence of differences in calculating the local government fiscal condition between that based on the Finance Minister Regulation (FMR) No. 266/2015 that using growth ratio, and Brown (1993) formulation that based on static ratio. The objective of this research was to analyze the differences among those two calculation methods and determine the actual valuation formula based on case studies from 26 regencies/districts in West Java. Descriptive analysis and Wilcoxon signed rank test was used to compare both calculation. The result showed that calculation based on FMR did not show the real fiscal condition of local government and also did not meet sense of fairness for regencies/districts with better fiscal condition, than Brown's (1993) formulation. Based on Wilcoxon signed rank test 72,73% of those all variable in FY 2016 calculation showed significant differences. The designed formula used to determine the fiscal condition in managing local government financial in this research was the combination of growth ratio calculation and static ratio by using weighted methods and quadrant method.